2016
DOI: 10.1002/2015ja022055
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chemical processes to infrared emissions from nitric oxide in the thermosphere

Abstract: Infrared emissions from nitric oxide (NO) are the dominant source of radiative cooling between 120 and 200 km and play an important role in determining the energy budget of the Earth's upper atmosphere. The emission arises as a consequence of producing vibrationally excited NO, either by collisions with energetic atomic oxygen or via the reaction of atomic nitrogen with molecular oxygen. The latter process is a potentially important source of cooling, as it can excite the higher vibrational levels (v ≥ 2) of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…The details are given in the appendix. As shown in Figure A1, the higher vibrational levels (v ≥ 2) of NO and the N 2 (A) have important contribution to the NO emission during quiet time, which is consistent with previous studies (Venkataramani et al, 2016;Yonker, 2013). However, they contribute little to the NO production during storm time and the thermosphere recovery in this event.…”
Section: Methodology and Model Descriptionsupporting
confidence: 92%
See 3 more Smart Citations
“…The details are given in the appendix. As shown in Figure A1, the higher vibrational levels (v ≥ 2) of NO and the N 2 (A) have important contribution to the NO emission during quiet time, which is consistent with previous studies (Venkataramani et al, 2016;Yonker, 2013). However, they contribute little to the NO production during storm time and the thermosphere recovery in this event.…”
Section: Methodology and Model Descriptionsupporting
confidence: 92%
“…Besides collisions with oxygen atom, the excited NO also can be generated from reactions (R1) and (R2) in higher vibrational levels(v ≥ 2), which would radiate 5.3-μm emission and 2.7-μm overtone emission (Miquel et al, 2003;Sultanov & Balakrishnan, 2006). Venkataramani et al (2016) integrated the chemiluminescence, which resulted from chemical excitation NO, into the TIEGCM and demonstrated that the contribution of chemiluminescence constituted 30% of total NO emissions during quiet time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Venkataramani et al . [] modeled low‐latitude NO emission by calculating the populations of NO ( υ ≤ 10) given the reaction of N( 2 D) or N( 4 S) with O and O 2 . They found that for geomagnetic quiet conditions vibrationally ‐excited NO produced by N( 2 D) is the dominant source of the emission in the sunlit thermosphere, contributing on average ~85% of the emission between 100 and 200 km.…”
Section: Discussionmentioning
confidence: 99%